Comunidades componentes de helmintos de anfíbios: análise comparativa entre duas localidades sob ação antrópica no município de São Luiz do Paraitinga, SP - Schwartz, Helena de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
With the degradation of Atlantic Forest over the years, the area that this ecosystem has occupied before decreased and in a lot of cases it was separated in little fragments, each one isolated in a different way depending of the local antropic action. In this context, this study compares the helminth fauna of anurans from two different fragments of Atlantic Forest, one inset in a matrix of eucalyptus (Eucaliptus sp.) reforestation and the other in a matrix of pasture (Brachiaria sp.), verifying if there is any difference between the structure of helminth communities. There were collected 155 anurans in both fragments, being 77 Hypsiboas albopunctatus, 18 Hypsiboas faber, 27 Hypsiboas polytaenius e 33 Dendropsophus minutus. These were weighted and their snout-vent lengths were measured. After the animals were euthanatized and their internal organs and coelomatic cavity were evaluated for helminth infection. There were identified one trematode species (Haematoloechus fuelleborni) and 14 nematode species (Aplectana sp., Cosmocerca parva, Cosmocerca sp1., Cosmocerca sp2., Cosmocercoides sp., Falcaustra mascula, Cosmocercidae larvae, nematode larvae, Physaloptera sp. larvae, Ochoterenella sp., Oswaldocruzia subauricularis, Raillietnema simples, Rhabdias sp. e Schrankiana sp.). The hylids' helminth fauna studied in São Luiz do Paraitinga fragments were relatively rich, being registered 15 helminth species in the captured anurans. The comparison between the fragments did not show differences in relation of the composition and abundance of helminth fauna in spite of the individualities of each environment

Com a degradação da Mata Atlântica ao longo dos anos, a área que esse ecossistema ocupava diminuiu e em muitos casos foi separada em pequenos fragmentos, cada qual isolado de maneira diferente dos demais dependendo da ação antrópica local. Nesse contexto, este estudo compara a helmintofauna de anuros residentes em dois fragmentos de Mata Atlântica, um inserido em uma matriz de eucaliptos (Eucaliptus sp.) e outro em uma matriz de pasto (Brachiaria sp.), verificando se existe diferença na estrutura das comunidades de helmintos. Foram coletados através de busca ativa 155 anuros nos dois fragmentos analisados, sendo 77 Hypsiboas albopunctatus, 18 Hypsiboas faber, 27 Hypsiboas polytaenius e 33 Dendropsophus minutus. Estes foram pesados, tiveram seu comprimento-rostro-clocal (CRC) medido e em seguida foram eutanasiados e tiveram seus órgãos internos e sua cavidade celomática avaliados quanto à presença de helmintos. Foram identificadas uma espécie de trematódeo (Haematoloechus fuelleborni) e 14 espécies de nematódeos (Aplectana sp., Cosmocerca parva, Cosmocerca sp1., Cosmocerca sp2., Cosmocercoides sp., Falcaustra mascula, Larva de Cosmocercidae, Larva de nematóide, Larva de Physaloptera sp., Ochoterenella sp., Oswaldocruzia subauricularis, Raillietnema simples, Rhabdias sp. e Schrankiana sp.. A helmintofauna dos hilídeos estudados nos fragmentos de São Luiz do Paraitinga mostrou-se relativamente rica, sendo registrada 15 espécies de helmintos nos anuros capturados. A comparação entre os fragmentos não demonstrou diferença com relação à composição e abundância da helmintofauna apesar das individualidades de cada ambiente
Keywords: Helmintologia veterinaria; Anfíbio; Anuro